MANAJEMEN RISIKO PENANGANAN BANJIR PADA SISTEM JARINGAN DRAINASE DI WILAYAH KOTA DENPASAR - Purbawijaya, Ida Bagus Ngr (Jurnal Ilmiah Teknik Sipil, 2012)
Recently, the infrastructure condition of drainage network system in Denpasar cannot overcome flood problem which happens every rainy season. This problem has been resulted due to lack of drainage network system management related to the increasing in housing area development, the changing of land use, and other activities which cause risk of flood. One of the causes, i.e. risk identification especially for major risks has not yet been available as a base to undertake mitigation of consequences. Therefore, there is a need to conduct a study on drainage network system, in order to control the risks that are likely occurred and particularly has widely affected to the aspect of planning, development, operational and maintenance. This research identified 91 risks, including 13 risks found from previous study. The distribution of risk acceptance for planning, operational and maintenance of flood mitigation in Denpasar is classified as unacceptable risk by 27 (29,67%); undesirable risks by 26 (28,57%); acceptable risks by 35 (38,46%); and negligible risks by 3 (3,30%). Risk mitigation is only conducted for dominant risks that are categorized as unacceptable and undesirable risks. There are 27 of risk mitigation conducted for unacceptable risks, that covers 10 (37,04%) of planning risks, 4 (14,81%) of execution risks and 13 (48,15%) of maintenance and operasional risks. Risk mitigation for undesirable categories consist of 26 risks; these are 10 (38,46%) of planning risks, 7 (26,92%) execution risks and 9 (34,62%) of operasional and maintenance risks. Subsequently, management of risk ownership is addressed to the parties that involved in flood mitigation in Denpasar.
Keywords: risk, identify risk, mitigation of risk, management of risk.